Boys’ violence in settler-colonial contexts: illegitimate civic duty and pathways to violence - Irwin, Katherine (Deviant behavior, 2023)
The data for this paper come from an 11-year participant observation study in a public high school in Hawaiʻi. The study included 25 interviews with working-class and poor boys of color, most of whom were of Pacific Islander ancestry. This manuscript considers whether everyday acts of violence among the boys in the study stemmed from common motivations that cut across race, gender, and class divides. The study also explored whether the boys’ violence could be tied to historic, multifaceted inequalities within the settler-colonial order of Hawaiʻi. The boys authored a form of violence that can be called "illegitimate civic duty," which allowed them to demonstrate their alignment with mainstream nationalist ideologies and masculinity norms. In some ways, the boys’ violence in enacting their civic duty could be tied to common motivations that affect boys across the U.S. In other cases, however, the boys’ use of violence could be linked with their unique consciousness and view of the historic injustices embedded in the settler-colonial system of Hawaiʻi. The findings are used to weave together general and subgroup-specific perspectives on male violence.